Measurement of exclusive γγ →W+W- production and search for exclusive Higgs boson production in pp collisions at √s = 8 TeV using the ATLAS detector - Alconada Verzini, María Josefina (2016)
Searches for exclusively produced W boson pairs in the process pp(γγ)→pW+W-p and an exclusively produced Higgs boson in the process pp(gg)→pHp have been performed using e±μ∓ final states. These measurements use 20.2 fb-1 of pp collisions collected by the ATLAS experiment at a center-of-mass energy √s = 8 TeV at the LHC. Exclusive production of W+W- consistent with the Standard Model prediction is found with 3.0σ significance. The exclusive W+W- production cross section is determined to be σ(γγ→W+W-→e±μ∓X) = 6.9 ± 2.2(stat) ± 1.4(sys) fb, in agreement with the Standard Model prediction. Limits on anomalous quartic gauge couplings are set at 95% confidence level as -1.7×10-6<aW0/Λ2<1.7×10-6 GeV-2 and -6.4×10-6<aWC/Λ2<6.3×10-6 GeV-2. A 95% confidence-level upper limit on the total production cross section for an exclusive Higgs boson is set to 1.2 pb.